A study on the contamination routes of tomato and bell pepper plants by Escherichia coli and Listeria innocua - Neetoo, Swaleha Hudaa; Ganeshan, Seelavarn (JOURNAL OF ADVANCES IN AGRICULTURE, 2015)
Tomatoes and bell peppers have been the source of recent outbreaks of foodborne illnesses due to contamination by human pathogens such as E. coli O157:H7 and Listeria monocytogenesin the field. The objectives of the present study were to investigate (i) the potential uptake of bacterial surrogates of E. coli O157:H7 and Listeria monocytogenes, E. coli(EC) and L. innocua(LI), from soil into the edible parts of tomato and pepper plants, and (ii) the survivability of EC and LI in the plant environment (soil, rhizosphere and phyllosphere).Mature tomato and bell pepper plants were soil-inoculated with a bacterial suspension(population density of ca. 108 cfu/ml) ofNalidixic-acid resistant EC or LI. Tomatoes and pepperswere also artificially contaminated on the surface with 1 ml of an overnight culture of Nalidixic-acid resistant EC and LI (population density of ca. 109cfu/ml). Samples of vegetables as well as non-edible parts (soil, roots, stem, foliage) were subjected to microbiological analyses by plating on Eosin Methylene Blue Agar and Listeria Identification Agar supplemented with Nalidixic acid to a final concentration of 50 mg/ml to recover EC and LIrespectively. We observed no evidence of internalization of EC or LI into the edible fruits. However, these bacteria were recovered from different non-edible parts of the tomato plant at varying population densities of 3.0-3.6, 1.8-2.2 and < 0.7 log cfu/g in the bulk soil, roots and foliage respectively. They were also found to persist in the soil for up to 4 days post-inoculation. Tomatoes and peppers surface-inoculated with EC or LI were shown to harborthe bacteria for > 48 h.Â  Taken together, findings of this study point to the microbiological and health risks associated with consumption of raw tomatoes and bell peppers due to the possibilities of pre-harvest microbial contamination by human pathogens.